2007
DOI: 10.1029/2007gl029599
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of model and GRACE estimates of the large‐scale seasonal cycle in ocean bottom pressure

Abstract: [1] Seasonal variability in ocean bottom pressure p b is analyzed using GRACE (Gravity Recovery and Climate Experiment) data products and an optimized model solution obtained by fitting most available ocean data in a leastsquares sense. The annual cycle in the spatial mean is a substantial part of the observed seasonal p b variability; net freshwater input and atmospheric pressure effects are both important. For the residual spatially-varying patterns, GRACE and model results agree well over the Southern Ocean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
64
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 21 publications
9
64
0
Order By: Relevance
“…Estimates of oceanic mass and velocity fields produced by ECCO have been used to interpret geodetic measurements of Earth's orientation in space and its variable gravity field, and to highlight the major role of ocean angular momentum variability in explaining observed polar motion (e.g., Gross et al, 2005;Ponte et al, 2001Ponte et al, , 2007a. Comparisons with the geodetic data provide entirely independent tests of the ECCO results.…”
Section: Earth Rotation and Geodesymentioning
confidence: 99%
“…Estimates of oceanic mass and velocity fields produced by ECCO have been used to interpret geodetic measurements of Earth's orientation in space and its variable gravity field, and to highlight the major role of ocean angular momentum variability in explaining observed polar motion (e.g., Gross et al, 2005;Ponte et al, 2001Ponte et al, , 2007a. Comparisons with the geodetic data provide entirely independent tests of the ECCO results.…”
Section: Earth Rotation and Geodesymentioning
confidence: 99%
“…An analysis by Ponte et al (2007) concluded that the 750 km version had lowest residuals with another version of the ECCO model. If we compare the RL05 data smoothed with different Gaussian smoothers to the unsmoothed JPL ECCO OBP, we find that 500 km smoothed maps have significantly lower standard deviations (Fig.…”
Section: Analysis Of Release-05 Datamentioning
confidence: 99%
“…In order to make the models consistent with the GRACE observed OBP, we add the GRACE observation of monthly mean ocean mass to the JPL ECCO and OMCT grids before computing statistics. Moreover, JPL ECCO does not contain the time-variable global mean fluctuation in OBP due to changes in the mean atmospheric pressure over the ocean (e.g., Ponte et al, 2007), which is a 0.6 cm seasonal variation. This is included in the GAD coefficients (and so is also included in the GRACE observations).…”
Section: Review Of Release-04 Data Processing and Ocean Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trend is caused by the Boussinesq approximation that is used in the model, i.e. oceanic volume, and not mass, is held constant in the OGCM (Ponte et al 2007). The reader should be aware that real long-term variations in observed OBP are expected due to (1) trends in freshwater fluxes; (2) trends in the atmospheric forcing; and (3) real long-term variations in the large-scale circulation, i.e.…”
Section: Ocean Bottom Pressurementioning
confidence: 99%